INCIDENCE OF PLAY IN THE DEVELOPMENT OF SOCIAL SKILLS IN CHILDHOOD. - Ayda Dorany Fonseca Buitrago; Diana Milena Chaparro Suárez; Sonia Milena Velásquez Orozco (DIALÉCTICA, 2025)
This text explores the fundamental importance of play in the comprehensive development of the child, covering cognitive, socio-emotional and communicative aspects. The contributions of various theorists such as Vygotsky, Piaget, Bruner, Erikson, Dewey, and others are highlighted, who agree on the relevance of play as an educational tool, a process of deep learning and the development of social skills in preschool age. The game is presented as a space for creation, discovery and construction of identity, where the child internalizes cultural values, solves problems and connects with his environment. The role of the adult as a mediator is emphasized, facilitating development through play. The different theoretical perspectives converge on the idea that play is not a mere pastime, but an essential pillar for the adaptation and development of the child in their cultural context, enhancing their growth and well-being. The richness and complexity of play as a learning and development process is also highlighted, offering a comprehensive vision of its impact on the child's education.